ASUHAN KEPERAWATAN GANGGUAN PERSONAL HYGIENE PADA LANSIA DENGAN PENINGKATAN KADAR ASAM URAT DI PANTI WERDHA MOJOPAHIT MOJOKERTO TAHUN 2016 - Yunita Novi Sujarwati (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2017)
Personal hygiene is a self-care that is done to maintain health. Personal hygiene is the first step in realizing health. Elderly people especially should be encouraged to carry out personal hygiene routinely. The purpose of this case study was applying the nursing care for poor personal hygiene in elderly with elevated uric acid levels. This case study used observation and interview methods that submitted to the client by using the geriatric nursing care format. Respondents of personal hygiene, namely the elderly aged 75-80 years as many as 2 respondents. from the results of the assessment on the client with poor personal hygiene characterized by client's dirty hair, unkempt, body odor, long and dirty nails, ears were not cleaned, dental caries and bad breath. On both clients obtained the same signs and symptoms so that the nursing problems that arose on both the clients was poor personal hygiene interventions and implementation were done by bathing the client, the client's hair combed, cut the nails, washed clients hair and examination of uric acid on both clients. Evaluations were obtained from both the clients the problem of nursing problem partially resolved and in accordance with the purpose and results criteria.